Association of TGF-β2 Gene Polymorphism with Growth Rate in Local Chickens - Sahib, Ali M.; Al-Khalisy, Abbas F; Abdulwahid, Mushtaq T (The Iraqi Journal of Veterinary Medicine, 2021)
Iraqi native chickens have tasty meat and eggs; however, they are characterized by low production efficiency. In fact, phenotypic traits, such as growth rate, are influenced by genes and environmental factors. During health and disease, a variety of cellular processes such as proliferation, differentiation, motility, adhesion, migration, apoptosis, and immune response regulate the TGF-β genes. The enhancement in body weight can be reached through mass selection, whereas feed conversion ratio (FCR) is relatively more difficult to improve. This means, selecting for body weight has been submitted as an effective way of indirectly improving feed conversion ratio. Therefore, the present study attempts to identify associations between productive traits and polymorphism of TGF-β2 gene in local Iraqi chicken. Seventy-five male birds were used in this study. The restriction enzyme RsaI has been used to detect the target region (284 bp) in the TGF-β2 gene. A single nucleotide polymorphism (SNP) was identified at the position 62 in the exon 1 region of TGF-β2 by using PCR-RFLP and DNA sequencing technique. The genotypic frequencies were 46.7, 40, and 13.3% for CC and TC and TT genotypes, respectively. While the allele frequency of C and T were 0.67 and 0.33%, respectively. Generally, during the last period of rearing the best significant (P<0.05) improve in the body weight, weight gain and FCR were recorded in the TT genotype of the TGF-β2 gene. In conclusion, a functional sequence in the genome could be attributed to the mutation. Therefore, genotype of the TGF-β2 gene could be exploited to select the best individual as a parent to the next generations for improving of growth rate in